Pediococcus acidilactici F-11 Penghasil Bakteriosin sebagai Agensia Biokontrol Escherichia coli dan Staphylococcus aureus pada Sayuran Segar Simpan Dingin - Endang Sri Rahayu; Eni Harmayani; Tyas Utami; Kejora Handarini (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Our survey indicated that fresh vegetables contained. high population of microorganisms including pathogenic Staphylococcus aureus. Washing procedures, including the addition of sanitizes to the wash water have not been effectively in reduction of the number of microorganisms. Currently, there is interest in possible use bacteriocin producer of lactic acid bacteria as biocontrol agents to ensure safety of minimally processed, refrigerated (MPR) foods which are not acidified, including fruits and vegetables. Our previous result, indicated that Pediococcus acidilactici F-11 (PAF-11) produced bacteriocin with wide spectrum activity. Objectives of this research was to study the potency of PAF-I 1 as biocontrol agent to inhibit the growth of pathogenic bacteria occurred in ready to eat fresh vegetables, i.e., paprika, lettuce, carrot. The results showed that PAF-11 was able to inhibit the growth of naturally present coliform and Staphylococcus significantly, as well as that of tested bacteria of E. coil and S. aureus which were inoculated into paprika and carrot. PAF-11 was able to grow at these two vegetables, and their population were increased about I log cycle. Bacteriocin activity produced by PAF-11 was positively detected from these two vegetables inoculated with these bacteria. However, there was no inhibition activity of PAF-11 against naturally present coliform and Staphylococcus, as well as inoculated E. coil and S. aureus on lettuce. Bacteriocin activity produce by PAF-11 was also not detected in this vegetables. Conclusion of this study, Pediococcus acidilactici F-11 could be used as biocontrol agents in paprica and carrot.